PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERBANTUAN E-LKPD UNTUK MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA SISWA - Ni Putu Diah Apriyantini; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Differentiated learning is learning that is designed with the aim of facilitating all the diversity of students based on the learning needs and characteristics of students in learning activities. E-LKPD in the form ofLive Worksheet is one of the media assisted by electronic media which contains text, images, animations, and videos that are more effective so that students don't get bored quickly. The purpose of this study was to find out whether the application of E-LKPD-assisted differentiated learning can increase students' active learning in mathematics. This type of research is Classroom Action Research. The subjects of this research were class VIII.2 students of SMP Negeri 6 Denpasar in the academic year 2022/2023 and the object of this research was the activeness of students learning mathematics. In this research through two cycles consisting of four stages of the activity process which includes (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques using the observation method. The results of the study show that the application of E-LKPD-assisted differentiated learning can increase the activeness of learning mathematics in class VIII.2 students of SMP Negeri 6 Denpasar in the 2022/2023 academic year